2020
DOI: 10.1177/1542305020916721
|View full text |Cite
|
Sign up to set email alerts
|

Premarital Counseling Practices among Christian and Muslim Lay Counselors in Ghana

Abstract: We examined premarital counseling services offered by Christian and Muslim lay counselors in Ghana. Participants including clergy, Islamic clerics, and laity practicing in four urban centers were interviewed. Thematic analysis showed that common issues covered include medical screening, beliefs and values, expectations, partner knowledge, roles and duties, sex, parenthood, financial management, communication, and conflicts. The findings offer important insight into religious premarital counseling in Ghana and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
4
0
8
Order By: Relevance
“…The results of Research question 1 revealed that even though the content of the premarital counselling in the study area was quite comprehensive, the most sufficiently discussed topics included 'communication in marriage', 'respect, understanding and appreciation in marriage' and 'how to play marital roles'. This finding seems to partially confirm Osei-Tutu et al [17] who inter alia reported that the most common issues covered in premarital counselling included medical screening, beliefs and values, expectations, partner knowledge, roles and duties, sex, parenthood, financial management, communication, and conflicts.…”
Section: Discussionsupporting
confidence: 78%
“…The results of Research question 1 revealed that even though the content of the premarital counselling in the study area was quite comprehensive, the most sufficiently discussed topics included 'communication in marriage', 'respect, understanding and appreciation in marriage' and 'how to play marital roles'. This finding seems to partially confirm Osei-Tutu et al [17] who inter alia reported that the most common issues covered in premarital counselling included medical screening, beliefs and values, expectations, partner knowledge, roles and duties, sex, parenthood, financial management, communication, and conflicts.…”
Section: Discussionsupporting
confidence: 78%
“…They are the main custodians of religion and liturgical practices. Additionally, they provide emotional and psychological support in diverse forms to people during times of crisis (Asamoah et al, 2014 ; Benyah, 2020 ; Osei-Tutu et al, 2019 , 2020 ).…”
mentioning
confidence: 99%
“…Of particular interest are places of existing tension and overlap with other health infrastructure and practices. This could be in the context of the process study of collaborative programs, as in this study, or in existing congregational settings like church counseling practices (van Dijk, 2013 ; Osei-Tutu et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%